Self-decoration of Pt metal particles on TiO2 nanotubes used for highly efficient photocatalytic H2 production - Basahel, Sulaiman N.; Lee, Kiyoung; Hahn, Robert; Schmuki, Patrik; Bawaked, Salem M.; Al-Thabaiti, Shaeel A. (Chemical Communications, 2014)
Pt decorated TiO2 has, over the past decades, been a key material for photocatalytic hydrogen production. The present work shows that growing anodic self-organized TiO2 nanotubes from Ti-Pt alloy with a low Pt content of 0.2 at% leads to oxide nanotube layers that are self-decorated with Pt nanoparticles of 4-5 nm in diameter. The average particle spacing is in the range of 50 nm and is partially adjustable by the anodization conditions. This intrinsic decoration of TiO2 nanotubes with Pt leads to a highly active photocatalyst for the production of H2 under UV or visible light conditions.
EAM Import::2019-03-13